Recalibration and External Validation of the Risk Analysis Index: A Surgical Frailty Assessment Tool. Issue 6 (December 2020) - Arya, Shipra; Varley, Patrick; Youk, Ada; Borrebach, Jeffrey D.; Perez, Sebastian; Massarweh, Nader N.; Johanning, Jason M.; Hall, Daniel E.
Abstract : Objective and Background: The Risk Analysis Index (RAI) predicts 30-, 180-, and 365-day mortality based on variables constitutive of frailty. Initially validated, in a single-center Veteran hospital, we sought to improve model performance by recalibrating the RAI in a large, veteran surgical registry, and to externally validate it in both a national surgical registry and a cohort of surgical patients for whom RAI was measured prospectively before surgery. Methods: The RAI was recalibrated among development and confirmation samples within the Veterans Affairs Surgical Quality Improvement Program (VASQIP; 2010–2014; N = 480, 731) including major, elective noncardiac surgery patients to create the revised RAI (RAI-rev), comparing discrimination and calibration. The model was tested externally in the American College of Surgeons National Surgical Quality Improvement Program dataset (NSQIP; 2005–2014; N = 1, 391, 785), and in a prospectively collected cohort from the Nebraska Western Iowa Health Care System VA (NWIHCS; N = 6, 856). Results: Recalibrating the RAI significantly improved discrimination for 30-day [ c = 0.84–0.86], 180-day [ c = 0.81–0.84], and 365-day mortality [ c = 0.78–0.82] ( P < 0.001 for all) in VASQIP. The RAI-rev also had markedly better calibration (median absolute difference between observed and predicted 180-day mortality: decreased from 8.45% to 1.23%). RAI-rev was highly predictive of 30-day mortality ( c = 0.87) in external validation with excellent calibration (median absolute difference between observed and predicted 30-day mortality: 0.6%). The discrimination was highly robust in men ( c = 0.85) and women ( c = 0.89). Discrimination also improved in the prospectively measured cohort from NWIHCS for 180-day mortality [ c = 0.77 to 0.80] ( P < 0.001). Conclusions: The RAI-rev has improved discrimination and calibration as a frailty-screening tool in surgical patients. It has robust external validity in men and women across a wide range of surgical settings and available for immediate implementation for risk assessment and counseling in preoperative patients. Abstract : Supplemental Digital Content is available in the text